A Unique Cellular and Molecular Microenvironment Is Present in Tertiary Lymphoid Organs of Patients with Spontaneous Prostate Cancer Regression - García-Hernández, María de la Luz; Uribe-Uribe, Norma Ofelia; Espinosa-González, Ricardo; Kast, W. Martin; Khader, Shabaana A.; Rangel-Moreno, Javier (Frontiers in Immunology, 2017)
Abstract. Objective: Multiple solid cancers contain tertiary lymphoid organs (TLO). However, it is unclear whether they promote tumor rejection, facilitate tumor evasion, or simply whether they are a byproduct of chronic inflammation. We hypothesize that although chronic inflammation induces TLO formation, the tumor milieu can modulate TLO organization and functions in prostate cancer. Therefore, our study seeks to elucidate the cellular and molecular signatures in unique prostatectomy specimens from evanescent carcinoma patients to identify markers of cancer regression, which could be harnessed to modulate local immunosupression or potentially enhance TLO function. Methods: We used multicolor immunofluorescence to stain prostate tissues, collected at different stages of cancer progression (prostatic intraepithelial neoplasia, intermediate and advanced cancer) or from patients with evanescent prostate carcinoma. Tissues were stained with antibodies specific for pro-inflammatory molecules (cyclooxygenase 2, CXCL10, IL17), tumor infiltrating immune cells (mature DC-LAMP+ dendritic cells, CD3+ T cells, CD3+Foxp3+ regulatory T cells, T bet+ Th1 cells, granzyme B+ cytotoxic cells), and stromal cell populations (lymphatic vessels, tumor neovessels, high endothelial venules, stromal cells), which promote prostate tumor growth or are critical components of tumor-associated TLO. Results. Generally, inflammatory cells are located at the margins of tumors. Unexpectedly, we found TLO within prostate tumors from patients at different stages of cancer, and in unique samples from patients with spontaneous cancer remission. In evanescent prostate carcinomas, accumulation of regulatory T cells (Treg) was compromised, while Tbet+ T cells and CD8 T cells were abundant in tumor-associated TLO. In addition, we found a global decrease in tumor neovascularization and the coverage by cells positive for cyclooxygenase 2 (COX2). Finally, consistent with tumor regression, PSCA antigen was considerably reduced in TLO and tumor areas from evanescent carcinoma patients. Conclusion. Collectively, our results suggest that COX2 and Treg are attractive therapeutic targets that can be harnessed to enhance TLO-driven tumor immunity against prostate cancer. Specially, the presence of high endothelial venules and lymphatics indicate that TLO can be used as a platform for delivery of cell-based and/or COX2 blocking therapies to improve control of tumor growth in prostate cancer.